Traumatic hand injury management and outcomes: A case report - Monique M. Keller; Pieter W. Jordaan (South African Family Practice)
Acute hand injuries are routinely managed by family medicine and primary care physicians. An appropriate initial assessment and treatment, early referral to a hand surgeon when indicated, and timeous referral to a hand therapist are imperative. A patient case report is presented reporting on the initial and subsequent assessment, treatment and outcomes at 3, 6, 7 and 9 months for a patient who sustained an acute finger injury. Finger range of motion (ROM), sensation, pain, time of wound closure, hand function measured with the standardised disability of the shoulder, arm and hand (DASH) questionnaire were the outcomes used. Pain, crepitus, decreased sensation, decreased ROM right index finger proximal interphalangeal joint (PIPJ) and dense scarring was measured at 9 months. Missed injuries or lack of recognition of injury severity leads to delayed referral to specialist hand surgeons and therapists, which lengthens recovery time and leads to sub-optimal outcomes. This article aims to provide the primary care practitioner with the initial management of a patient who sustained a traumatic hand injury whilst using a power tool.